Balancing history, people, & place: adaptive preservation of Paseo Boulevard in Kansas City, Missouri - Wendling, Mackenzie D. (Kansas State University, 2019)
To be active and valued public spaces all urban landscapes, especially historic, must be adaptable to the dynamic sociocultural, environmental, and economic conditions of their context. Historic preservation is often met with deference to the past over the needs of the present. This is true of Dr. Martin Luther King Jr. Boulevard in Kansas City, Missouri. Formerly known as Paseo Boulevard, MLK Jr. Boulevard was the first parkway of Kansas City’s world-famous Parks and Boulevard system. This report and the resulting projective designs balance historic preservation and community needs on the cultural landscape. The mixed-method study collected data through historical map and image analysis, stakeholder interviews and a public survey. The data were synthesized and used to inform design interventions. The objectives of the research-informed designs are twofold. One, through creative placemaking they communicate the multi-narrative histories of Paseo Boulevard north of 18th Street. Two, designs aim to increase the landscape’s use-value by proposing a variety of culturally relevant programming. The results of the study have the opportunity to inform policy and design of Paseo Boulevard north of 18th Street in Kansas City, Missouri.
Keywords: Adaptive preservation; Historic preservation; Landscape architecture; Cultural landscape; Kansas City, Missouri; Paseo Boulevard